(untitled) (Research, Society and Development, 2021)
The layers of landfill cover have the function of preventing the entry of liquids as well as preventing the escape of gases. They are usually built with compacted clay soils and have low hydraulic conductivity. In this sense, this research aims to evaluate the feasibility of using mixtures of construction and demolition waste (RCD) with soil, to be used as a hydraulic barrier in the final coverage of landfills. For this, a clayey soil from an old clay extraction area that was deactivated for more than 30 years was used, on a slope located on the Island of Itamaracá-PE, Metropolitan Region of Recife (RMR). The mixtures used were 10%, 30% and 50% soil and RCD. The research program included physical, mechanical and mineralogical characterization tests, in addition to erodibility tests. In the physical characterization tests, the soil was classified with a clay of high plasticity and the RCD as a sandy material, whose addition to the soil caused a decrease in the fine content of the soil until it reached a medium plastic clay, results which were confirmed in the tests Atterberg Limits. The saturated hydraulic conductivities of the soils and mixtures were in the order of 10-9m/s. The parameters of resistance to simple compression of the mixtures were higher than the maximum resistance of the soil, having reached its highest value in the mixture of 30%. Regarding erodibility, the crumb test and pinhole test indicated that the studied soil does not present an erodible tendency. The addition of RCD decreases the expandability of the soil. Thus, it is concluded that mixing this specific soil from the region with the RCD is feasible for use as a hydraulic barrier, with the 50% mixture having the best results.